Effect of Lippia alba and Cymbopogon citratus essential oils on biofilms of Streptococcus mutans and cytotoxicity in CHO cells - Tofiño Rivera, Adriana Patricia (2016)
Background: Caries is a public health problem, given that it prevails in 60 to 90% of the school-age global population. Multiple factors interact in its etiology, among them dental plaque is necessary to have lactic acid producing microorganisms like Streptococcus from he Mutans group. Existing prevention and treatment measures are not totally effective and generate adverse effects, which is why it is necessary to search for complementary strategies for their management. Aim: The study sought to evaluate the eradication capacity of Streptococcus mutans biofilms and the toxicity on eukaryotic cells of Lippia alba and Cymbopogon citratus essential oils. Methodology: Essential oils were extracted from plant material through steam distillation and then its chemical composition was determined. The MBEC-high-throughput (MBEC-HTP) (Innovotech, Edmonton, Alberta, Canada) assay used to determine the eradication concentration of S. mutans ATCC 35668 strain biofilms. Cytotoxicity was evaluated on CHO cells through the MTT cell proliferation assay. Results: The major components in both oils were Geraniol and Citral; in L. alba 18.9% and 15.9%, respectively, and in C. citratus 31.3% and 26.7%. The L. alba essential oils presented eradication activity against S. mutans biofilms of 95.8% in 0.01 mg/dL concentration and C. citratus essential oils showed said eradication activity of 95.4% at 0.1, 0.01 mg/dL concentrations and of 93.1% in the 0.001 mg/dL concentration; none of the concentrations of both essential oils showed toxicity on CHO cells during 24 h. Conclusion: The L. alba and C. citratus essential oils showed eradication activity against S. mutans biofilms and null cytotoxicity, evidencing the need to conduct further studies that can identify their active components and in order to guide a safe use in treating and preventing dental caries.